PENGARUH WAKTU PEMBUNGAAN TERHADAP PRODUKSI BUAH DAN BENIH ACACIA HIBRID DI KEBUN PERSILANGAN Acacia mangium X Acacia auriculiformis - Sri Sunarti (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
Observation of seed production and hybrid seed yield were assessed in hybridization orchard of Acacia mangium x Acacia auriculiformis on the first and second flowering season . The hybridization orchard was established in 2006 using 6 selected plus trees from the first-generation of progeny test of A. mangium and 12 selected plus trees from the first-generation of progeny test of A.auriculiformis. Crosses were conducted using 2 spikes for each cross. Based on synchronization in flowering time, 6 and 17 crossing combinations were made resulting in 23 and 89 hybrid families in the first and second flowering seasons respectively. The average number of pods and seeds in the first flowering season were 1.9 pods/spike and 2.0 soundseed/pod respectively, while those in the second flowering time were increased to 2.6 pods/spike and 2.4 soundseeds/pot respectively. The percentage of poorseeds almost the same on the first and second flowering seasons, namely 28 .7% and 32.0% respectively. Verification using SCAR marker indicated that almost all of collected seeds were hybrid seeds.